Ultrastructural Studies of Involuting Bursa and Thymus of Giriraja Birds (Gallus domesticus) - Chandrasekhar, Leena; Prasad, R.V.; Jamuna, K.V. (International Journal of Poultry Science, 2012)
The ultra structural changes of involuting cells of bursa of fabricius and thymus could be classified as nuclear and cytoplasmic changes. Major cytoplasmic changes include arrangement of cytoskeletal filaments in parallel arrays, cytoplasmic membrane blebbing and dilatation of endoplasmic reticulum. Nuclear changes included clumping of chromatin, elongation and appearance of convolutions of the nuclear membrane with karyorrhexis, karyolysis and nucleolar disintegration. There is consequent cell volume reduction, detachment of cell from surroundings, formation of several membrane bound apoptotic bodies and its ingestion by neighboring cells.